Video Head Impulse Tests with a Remote Camera System: Normative Values of Semicircular Canal Vestibulo-Ocular Reflex Gain in Infants and Children - Wiener-Vacher, Sylvette R.; Wiener, Sidney I. (Frontiers in Neurology, 2017)
The Video Head Impulse Test (VHIT) is widely used to identify semicircular canal function impairments in adults. But classical VHIT testing systems attach goggles tightly to the head, which is not tolerated by infants. Remote video detection of head and eye movements resolves this issue and here we report VHIT protocols and normative values for children. VOR gain was measured for all canals of 303 healthy subjects including 274 children (aged 2.6 months to 15 years) and 26 adults (aged 16 to 67). We used the Synapsys® (Marseille, France) VHIT Ulmer system whose remote camera measures head and eye movements. HITs were performed at high velocities. Testing typically lasts 5-10 minutes. In infants as young as 3 months old VHIT yielded good inter-measure replicability. VOR gain increases rapidly until about the age of 6 years (with variation among canals) then progresses more slowly to reach adult values by the age of 16. Values obtained are more variable among very young children and for the vertical canals, but showed no difference for right vs. left head rotations. VHIT reliably measures VOR in very young children. Normative values of VOR gain are presented to help detect vestibular impairment in patients. VHIT testing prior to cochlear implants could help prevent total vestibular loss and the resulting grave impairments of motor and cognitive development in patients with residual unilateral vestibular function.